Improving Multitiered Systems of Support for Students With "Internalizing" Emotional/Behavioral Problems. (July 2018) - Weist, Mark D.; Eber, Lucille; Horner, Robert; Splett, Joni; Putnam, Robert; Barrett, Susan; Perales, Kelly; Fairchild, Amanda J.; Hoover, Sharon
A recently defined interconnected systems framework (ISF) provides explicit guidance on steps to align positive behavioral interventions and supports (PBIS) and expanded school mental health (SMH) within the multitiered system of support (MTSS). As PBIS and SMH strategies align, there are opportunities to expand and improve effective programs and services for students at all tiers of the MTSS. A prominent need is to improve programs and services for students presenting "internalizing" disorders such as those related to trauma, depression, and anxiety. In this article, we discuss relevant issues involved in improving multitiered systems/interventions for students presenting internalizing problems and provide guidance for this work in dimensions of cross-system collaboration (with major emphasis on effective teams), implementing evidence-based practices, and data-based decision making/quality improvement. The article concludes with recommendations for practice, research, and policy to improve MTSS for students presenting internalizing problems.